AN ANALYSIS ON THE ISLAMOPHOBIC ACTS IN FRANCE POST-ARAB SPRING - Hadza Min Fadhli Robby; Aathifah Amrad (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
The discourse of Islamophobia in Europe has become increasingly popular after the endless war in the Middle East. The instability that hit the Middle East after Arab Spring and the civil war in Syria has forced some of its population to migrate to European countries, including France. The large number of immigrants who have entered France has also been accompanied by rampant acts of attacks and terrorism, thereby revives the feelings of Islamophobia among the native white French. Meanwhile, Front National as an ultranationalist party known for its racist anti-immigrant policies has gained more influences in France by using Islamophobic narratives. In its political campaign, Front National uses the concepts of Laicite to corner French Muslim in the public sphere. The presence of French Muslim community is considered as a threat toward secular values and Christian civilization. In this study, the author will analyze the increase of Islamophobia which has been triggered by the immigrant crisis and the influence of the right-wing movement. The concept of race by W. Thomas Schmid will serve as a theoretical framework to answer the increasing Islamophobia in France. To conduct the research, the author uses the qualitative method to analyze texts and narratives related to the Islamophobia acts in France. This research concluded with a statement that Islamophobia in France post-Arab Spring generally occurs in three aspect: cognitive, motivational and behavioral aspects. A tendency of certain groups in the French society which looks Islam as a racial problem becomes one of the main roots of the rise of Islamophobia in France. Wacana Islamofobia di Eropa berkembang pesat, didorong oleh intensitas konflik di Timur Tengah yang tidak berkesudahan. Instabilitas yang melanda kawasan Timur Tengah pasca Arab Spring dan perang saudara di Suriah mendorong sebagian besar penduduknya untuk melakukan imigrasi ke berbagai wilayah di Eropa, termasuk Perancis. Hal ini membangkitkan kembali perasaan Islamofobia di beberapa kalangan penduduk Perancis yang berkulit putih. Dalam kondisi ini, Front National sebagai partai ultra-nasionalis menjadikan narasi-narasi Islamofobia untuk merebut pengaruh dalam politik Perancis. Front National juga menggunakan konsep Laicite untuk menyudutkan masyarakat Muslim di ranah publik. Kehadiran kelompok Muslim di tengah-tengah penduduk Perancis dianggap dapat mengancam nilai-nilai sekuler dan peradaban Kristen. Dalam tulisan ini, penulis akan menganalisis mengapa terjadi peningkatan Islamofobia yang dipicu akibat krisis imigran serta pengaruh gerakan sayap kanan. Penelitian ini menggunakan konsep Ras yang dikembangkan oleh W. Thomas Schmid. Dalam melakukan riset, penulis menggunakan metode kualitatif untuk mengkaji teks serta naskah-naskah yang terkait dengan tindakan Islamofobia di Perancis. Penelitian ini mengungkapkan bahwa Islamofobia di Perancis setelah Arab Spring terjadi dalam 3 aspek, yakni aspek kognitif, motivasional, dan behavioral. Adanya kecenderungan sebagian masyarakat Perancis memandang Islam sebagai masalah rasial menjadi akar penting yang menyebabkan berkembangnya Islamofobia di Perancis.